PENGARUH MINYAK ZAITUN (OLIVE OIL) TERHADAP KERUSAKAN INTEGRITAS KULIT PADA PASIEN DM TIPE II DI KECAMATAN PAGAR MERBAU - Kardina Hayati; Hana Setiani Mutiara; Dewi Agustina; Tahan Adrianus Manalu; Kuat Sitepu (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
ABSTRACT The success of changing the damage to the integrity of the skin in patients with Diabetes Mellitus Type II depends not only on early detection, but also on understanding the causative mechanism. One condition that can cause damage to the integrity of the skin is the xerosis and pruritus on skin . The purpose of this study to determine the effect of Oil Olive to damage the integrity of the skin in patients with DM type II in the District of Pagar Merbau . This type of research uses the Quasy Experiment Method using the One-Group Pretest-Posttest Design research design. Determination of the sample is done by purposive sampling, with a total sample of 22 people. Data analysis was performed using Paired Sample T Test with 95% confidence interval and Î± = 0.05. The results of this study indicate the change in damage to the integrity of the skin before and after given a basting oil olives with a p-value = 0.000 (Î±> 0.05). Conclusion, there is an influence of olive oil on damage to skin integrity in patients with type II DM in Pagar Merbau District which is carried out in accordance with standards. For Health Institutions the need for supervision and counseling to the community that the importance of maintaining skin health especially in patients with diabetes mellitus in Pagar Merbau District Keywords : Olive Oil , Skin Integrity Damage , Type II DM patients